Reappropriation of Western Tropes in Ayesha Muzaffar’s Jinnistan and The Bhabhis of Lahore: A Case for Pakistani Anglophone Paranormal Short Fiction - Yousaf, Subha (Journal of Research in Humanities, 2025)
This paper explores paranormal elements in Ayesha Muzaffar’s short story collections, Jinnistan (2023) and The Bhabhis of Lahore (2022), both of which are notable contributions to Pakistani Anglophone paranormal short fiction. The study investigates how religious and cultural influences shape the portrayal of paranormal creatures in Pakistani literature, with a specific focus on the reappropriation of Western paranormal tropes. While Western fiction often portrays possession through a Christian lens, Pakistani works reinterpret this theme using Islamic perspectives on jinn and maintain a distinctly South Asian supernatural aesthetic. Thus, the objective is to explore the distinct characteristics of Pakistani paranormal short fiction and how Western tropes are adapted within this framework.